Real-Time fast PCR amplification using designated and conventional real time thermal cycler systems: COVID-19 perspective. - Md Walid Hossain; Mohabbat Hossain; Khalid Arafath; Subarna Sayed Ety; Md Mahade Hasan Shetu; Mazbahul Kabir; Farjana Akther Noor; Kaiissar Mannoor (PLoS ONE)
The study aimed to shorten multiplex RT-PCR run time for detection of SARS CoV-2 N1 and N2 sequences and human RNase P (RP) sequence as internal mRNA control using conventional and designated real time thermal cycler systems. Optimization of Fast PCR protocol using plasmid-based N1 and N2 positive control and synthetic version of human RP was done on Applied Biosystems (ABI) QuantStudioTM5 (conventional), ABI 7500 Fast Dx (designated), and CFX96 Touch Real Time Detection System, Bio-Rad (conventional). Finally, a performance evaluation of Fast PCR was performed in terms of sensitivity, specificity, and precision. For a 40-cycle PCR with optimized Fast PCR protocols on QuantStudioTM5, ABI 7500 Fast Dx, and CFX96 Touch (conventional), standard/regular versus Fast PCR run times (min) were 84 vs. 49, 96 vs. 48, and 103 vs. 61, thereby saving 35, 48, and 43 min, respectively. For each thermal cycler, Standard and Fast PCR generated identical shapes of fluorescence curves, Ct values, and (3) R2 (0.95 to 0.99) for 5 10-log dilution panels of each positive control. The fast PCR approach generated results with 100% sensitivity and specificity. Median test comparisons between standard PCR and Fast PCR Cts of COVID-19 samples did not produce significance (p>0.5), suggesting that Fast PCR and Standard PCR were comparable. Also, the median and mean of each target had closely-related values, further suggesting that the two approaches were comparable. That is, there is an equivalency between Conventional and Fast PCR instruments for detection of COVID-19.